PENGARUH ASAM HUMAT DAN FULVAT EKSTRAK KOMPOS THITONIA DIVERSIFOLIA TERHADAP Hgkhelat, pH DAN C-ORGANIK ENTISOL TERCEMAR MERKURI - Sarifuddinn, Erdiansyah; Patadungan, Yosep Soge; Isrun, Isrun (AGROTEKBIS, 2017)
ABSTRACTÂ Entisols Palu including the area Poboya formed under the influence of a dry climate with the parent material which is dominated miniral quartz, very resistant to change arid climate causes weathering chemical reactions in the soil is slow, Activity processing of gold amalgamation using a mercury/mercury result in the loss of top fertile soil and polluted that will affect environmental conditions soil. Research is done to determine the effect of Humic and Fulvic Acid Extract Against Compost Thitonia diversifolia HgKhelat, pH and Org-C Entisol Contaminated Mercury. This study was arranged in a randomized block design (RBD) consisting of 6 dosage: control (without humic acid and fulvic acid), humic acid and fulvic acid at a dose of 50 ml/kg, 75 ml/kg, 100 ml/kg, 125 ml/kg, and 150 ml/kg soil, each treatment was repeated three times to obtain 18 units of experiment, results showed that the extract humic acid and fulvic acid compost Thitonia diversifolia up to a dose of 150ml/kg soil during incubation time for 30 days the significant and proven effective against changes in the Hgchelate were able to raise Hg-chelate, the pH of the soil and C-entisols Organic soil polluted with mercury.Â Key Words : Entisols Contaminated mercury, Humic acid and fulvic acid Tithonia,